AMÉRICA LATINA Y SU IDENTIDAD POLÃTICA: SOCIEDADES EN TRANSICIÃ“N EN LA ERA DE LA INTEGRACIÃ“N GLOBAL - Spadaro, Gabriela Scartascini; Melchor, Vilma Zoraida RodrÃguez (European Scientific Journal, ESJ, 2013)
This research analyzes the scope of the regional integration processes of Latin America countries, which are part of the resources of strategic positioning against the discourse of globalization. Government actions of Latin American countries is the political identity that, with a view of assessment of endogenous resources, further blocks of cooperation that are distinguished by the search and permanence of an emancipation in the different dimensions of human development of citizens living in these latitudes. Shared actions reflect a continental juncture that finds horizons to justice and social welfare in the global era, cystic between uniformity and the fragmentation,